Respuesta :
Answer:
0
Step-by-step explanation:
METHOD 1.
We know:
[tex]f\bigg(f^{-1}(x)\bigg)=x[/tex]
Therefore
[tex]f\bigg(f^{-1}(0)\bigg)=0[/tex]
METHOD 2.
[tex]\text{Find}\ f^{-1}(x)[/tex]
[tex]f(x)=3x+12\to y=3x+12[/tex]
exchange x to y and vice versa:
[tex]x=3y+12[/tex]
solve for y:
[tex]3y+12=x[/tex] subtract 12 from both sides
[tex]3y=x-12[/tex] divide both sides by 3
[tex]y=\dfrac{x-12}{3}\to f^{-1}(x)=\dfrac{x-12}{3}[/tex]
[tex]f\bigg(f^{-1}(x)\bigg)\to[/tex] replace x in f(x) with the expression[tex]\dfrac{x-12}{3}[/tex]
[tex]f\bigg(f^{-1}(x)\bigg)=3\cdot\dfrac{x-12}{3}+12=x-12+12=x[/tex]
[tex]f\bigg(f^{-1}(0)\bigg)\to[/tex] put x = 0 to [tex]f\bigg(f^{-1}(x)\bigg)=x[/tex]
[tex]f\bigg(f^{-1}(0)\bigg)=0[/tex]
METHOD 3.
[tex]\text{Find}\ f^{-1}(x)[/tex]
[tex]f^{-1}(x)=\dfrac{x-12}{3}[/tex]
Calculate the value of f ⁻¹(x) for x = 0:
[tex]f^{-1}(0)=\dfrac{0-12}{3}=\dfrac{-12}{3}=-4[/tex]
Calculate the value of f(x) for x = -4:
[tex]f(4)=3(-4)+12=-12+12=0[/tex]